A New Fiscal Rule : Should Israel 'Go Swiss?' - Symansky, Steven; Debrun, Xavier; Epstein, Natan (Washington, D.C. : International Monetary Fund, 2008)
We propose a fiscal rule that fulfills a specific debt reduction objective while maintaining significant fiscal flexibility-two overarching concerns in Israel. Not unlike the Swiss "debt brake," the rule incorporates an error-correction mechanism (ECM) through which departure from the debt objective affects binding medium-run expenditure ceilings. Two variants of our ECM rule are shown to be superior to a comparable deficit rule in terms of attaining the debt objective and allowing for fiscal stabilization while supporting medium-term expenditure planning. Given its relative sophistication, a proper implementation of the ECM rule requires supportive fiscal institutions, including independent input and assessment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet